2008
DOI: 10.1002/jcb.21658
|View full text |Cite
|
Sign up to set email alerts
|

Back‐regulation of six oxidative stress proteins with grape seed proanthocyanidin extracts in rat diabetic nephropathy

Abstract: Diabetic nephropathy (DN) is a major cause of morbidity and mortality in diabetic patients. To prevent the development of this disease and to improve advanced kidney injury, effective therapies directed toward the key molecular target are required. Grape seed proanthocyanidin extracts (GSPE) have been reported to be effective in treating DN, while little is known about the functional protein changes. In this study, we used streptozotocin (STZ) to induce diabetic rats. GSPE (250 mg/kg body weight/day) were admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 46 publications
(46 reference statements)
5
50
0
Order By: Relevance
“…Ulusoy et al have shown that grape seed increased TAS level and decreased TOS level in cyclosporine A-induced nephropathy. 20 In accordance with the findings of our study, Li et al 23 reported antioxidant features of grape seed in STZ-induced diabetic rats. Grape seed proanthocyanidin extract (GSPE) was shown to increase glutathione levels in pancreatic tissue of diabetic rats, resulting in decreased lipid peroxidation, and increased insulin sensitivity by directly affecting the insulin signaling pathways.…”
Section: Discussionsupporting
confidence: 92%
“…Ulusoy et al have shown that grape seed increased TAS level and decreased TOS level in cyclosporine A-induced nephropathy. 20 In accordance with the findings of our study, Li et al 23 reported antioxidant features of grape seed in STZ-induced diabetic rats. Grape seed proanthocyanidin extract (GSPE) was shown to increase glutathione levels in pancreatic tissue of diabetic rats, resulting in decreased lipid peroxidation, and increased insulin sensitivity by directly affecting the insulin signaling pathways.…”
Section: Discussionsupporting
confidence: 92%
“…GSPB2, as a natural dietary supplement, displays an anti-oxidative property and protects against diabetic complications. 13,[31][32][33] The results of the present study reveal that GSPB2 inhibited the AGE-induced proliferation and migration of HASMCs, and that UCH-L1 may be involved in this process via the inhibition of NF-B activity.…”
Section: Fig 2 Effects Of Gspb2 On the Cell Migration Of Age-stimulmentioning
confidence: 95%
“…37,38) A GSPE treatment has decreased the aortic pulse wave velocity and aortic medial thickness by reducing the expression of AGE and RAGE in diabetic aortas. 39) GSPE has also demonstrated protective effects against nephropathy, 32) retinopathy, 31) and damage to peripheral nerves 33) and the cerebral cortex 40) in STZ-induced diabetic rats. We found in this present study that HASMCs stimulated with AGEs had a higher migration cell number and increased proliferation when compared with unstimulated HASMCs in a dosedependent manner.…”
Section: Fig 2 Effects Of Gspb2 On the Cell Migration Of Age-stimulmentioning
confidence: 99%
“…[12][13][14] Moreover, GSPEs have cardiovascular, cerebullar, and renal protective effects. [15][16][17] Our previous experiments showed that GSPEs displayed anti-nonenzymatic glycation and anti-inflammation, reducing receptor of advanced glycation end product (RAGE) protein expression, leading to decreased expression of high level vascular cell adhesion molecule 1 induced by advanced glycation end products (AGEs) in endothelial cells. 18,19) In our present study, we examined the effects of AGEs on the diabetic aorta and evaluated the efficacy of aortic protection by GSPEs.…”
Section: )mentioning
confidence: 99%